Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1270/jsbbs.18010
|View full text |Cite
|
Sign up to set email alerts
|

Resynthesis of <i>Brassica juncea</i> for resistance to <i>Plasmodiophora brassicae</i> pathotype 3

Abstract: The oilseed crop Brassica juncea carries many desirable traits; however, resistance to clubroot disease, caused by Plasmodiophora brassicae, is not available in this species. We are the first to report the clubroot resistant resynthesized B. juncea lines, developed through interspecific crosses between a clubroot resistant B. rapa ssp. rapifera and two susceptible B. nigra lines, and the stability of the resistance in self-pollinated generations. The interspecific nature of the resynthesized B. juncea plants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Hagimori et al [ 54 ] carried out somatic hybridization between broccoli and radish and obtained hybrid offspring with 36 chromosomes, which could be used as bridge germplasm for subsequent CR broccoli cultivation. Hasan and Rahman [ 55 ] obtained the B. juncea which was resistant to race 3 of P. brassicae using the method of distant hybridization. Liu et al [ 56 ] identified three B. rapa with high resistance to Pb4 from 50 materials, which were then used as donor parents to cross with rapeseed, and obtained CR progenies.…”
Section: Discussionmentioning
confidence: 99%
“…Hagimori et al [ 54 ] carried out somatic hybridization between broccoli and radish and obtained hybrid offspring with 36 chromosomes, which could be used as bridge germplasm for subsequent CR broccoli cultivation. Hasan and Rahman [ 55 ] obtained the B. juncea which was resistant to race 3 of P. brassicae using the method of distant hybridization. Liu et al [ 56 ] identified three B. rapa with high resistance to Pb4 from 50 materials, which were then used as donor parents to cross with rapeseed, and obtained CR progenies.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the evolutionary history of the Brassica genus, valuable traits of interest already identified in diploid Brassica genomes have the potential to be exploited in amphidiploid Brassica species through modern genetic editing techniques, or via interspecific crossing/resynthesis. This approach was used to great effect when introducing clubroot disease resistance from B. rapa into B. juncea material, wherein natural resistance is not evident ( Hasan and Rahman, 2018 ) and to introduce turnip yellows virus resistance from Brassica oleracea and B. rapa into B. napus ( Greer et al, 2021 ). Potential therefore exists for the generation of enhanced TuMV-resistant B. juncea cultivars using resistances already identified on the “A” genome of other Brassica species via resynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…rapa ) ( Yu et al , 2021 ; Yang et al , 2022 ). Most of the resistance loci have been mapped to chromosomes A01, A02, A03, A06, and A08 of the A genome, with only a few being mapped to the B or C genome ( Matsumoto et al , 1998 ; Suwabe et al , 2003 , 2006 ; Hirai et al , 2004 ; Piao et al , 2004 ; Sakamoto et al , 2008 ; Werner et al , 2008 ; Ueno et al , 2012 ; Chen et al , 2013 ; Hatakeyama et al , 2013 ; Chu et al , 2014 ; Li et al , 2016 ; Yu et al , 2016 , 2017 , 2021 ; Huang et al , 2017 , 2019 ; Hasan and Rahman, 2018 ; Hirani et al , 2018 ; Pang et al , 2018 ; Chang et al , 2019 ; Laila et al , 2019 ; Fredua-Agyeman et al , 2020 ; Karim et al , 2020 ; Dakouri et al , 2021 ; Rahaman et al , 2022 ). To date, only two clubroot-resistance genes, Crr1a and CRa , have been isolated, and they both encode toll-interleukin-1 receptor, nucleotide binding site, and leucine-rich repeat (TIR-NBS-LRR, TNL) proteins ( Ueno et al , 2012 ; Hatakeyama et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%